Rapid and Reliable Assessment of the Contrast Sensitivity Function on an iPad - Dorr, Michael; Lesmes, Luis A.; Lu, Zhong-Lin; Bex, Peter J. (Investigative ophthalmology & visual science, 2013)
Letter acuity, the predominant clinical assessment of vision, is relatively insensitive to slow vision loss caused by eye disease. While the contrast sensitivity function (CSF) has demonstrated the potential to monitor the slow progress of blinding eye diseases, current tests of CSF lack the reliability or ease-of-use to capture changes in vision timely. To improve the current state of home testing for vision, we have developed and validated a computerized adaptive test on a commercial tablet device (iPad) that provides an efficient and easy-to-use assessment of the CSF. We evaluated the reliability, accuracy, and flexibility of tablet-based CSF assessment. Repeated tablet-based assessments of the spatial CSF, obtained from four normally-sighted observers, which each took 3 to 5 minutes, were compared to measures obtained on CRT-based laboratory equipment; additional tablet-based measures were obtained from six subjects under three different luminance conditions. A Bland-Altman analysis demonstrated that tablet-based assessment was reliable for estimating sensitivities at specific spatial frequencies (coefficient of repeatability 0.14-0.40 log units). The CRT- and tablet-based results demonstrated excellent agreement with absolute mean sensitivity differences <0.05 log units. The tablet-based test also reliably identified changes in contrast sensitivity due to different luminance conditions. We demonstrate that CSF assessment on a mobile device is indistinguishable from that obtained with specialized laboratory equipment. We also demonstrate better reliability than tests used currently for clinical trials of ophthalmic therapies, drugs, and devices.